2021
DOI: 10.1186/s12906-021-03442-8
|View full text |Cite
|
Sign up to set email alerts
|

Arecae pericarpium extract induces porcine lower-esophageal-sphincter contraction via muscarinic receptors

Abstract: Background Gastroesophageal reflux disease (GERD) is associated with lower esophageal sphincter (LES) incompetence. In some patients, GERD is refractory to acid reduction therapy which is the main treatment for GERD. So far, medications that can increase LES tone are few. Arecae pericarpium (A. pericarpium) is a medication in Traditional Chinese Medicine known to promote intestinal motility. Methods We investigated the effect of A. pericarpium extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, the muscarinic receptor antagonist atropine inhibited such contractions. These results showed that AN extract and arecoline induced contractions were mediated by muscarinic receptors indicating the possibility of developing as an alternative therapy for gastroesophageal reflux disease [71].…”
Section: Gastric and Intestinal Diseasesmentioning
confidence: 75%
“…However, the muscarinic receptor antagonist atropine inhibited such contractions. These results showed that AN extract and arecoline induced contractions were mediated by muscarinic receptors indicating the possibility of developing as an alternative therapy for gastroesophageal reflux disease [71].…”
Section: Gastric and Intestinal Diseasesmentioning
confidence: 75%
“…Numerous studies have investigated the impact of GPCRs on LES contraction and revealed important findings. For instance, extracts from Arecae pericarpium have been shown to induce contractions in the porcine LES, which are potentially mediated by muscarinic (M) receptors (Tey et al, 2021). Activation of bombesin receptor subtypes 2 and 3 has been identified as responsible for mediating tonic contraction of the porcine LES following bombesin stimulation (Tsai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the contraction of the lower esophageal sphincter caused by these extracts and arecoline was not affected by tetrodotoxin inhibition but was significantly suppressed by atropine. This suggests that the contractions of the porcine lower esophageal sphincter induced by the extracts and arecoline of the AN may be dose-dependent and mediated through muscarinic receptors [ 38 ].…”
Section: Biological Effectsmentioning
confidence: 99%